Investigation of Smart Tools in Order to Improve the Effectiveness of the Administration of Disaster Management I. (Academic Journal of Internal Affairs, 2021)
The security of a well-functioning country requires an administrative and defence management system. The author presents the operation and activity system of the Hungarian disaster management organizational system, paying special attention to the examination of smart devices that improve the efficiency of public administration. The author demonstrates in his research that the use of smart devices and technologies contributes to the reduction of disaster risk, damage, and helps disaster prevention. Based on the applied research methods, the author proves that due to the identified problems, the increasing number of inspections and the growing information society expectations require us to use the tools and technologies of disaster management authorities to strengthen the safety factors.
Keywords: e-governance; disaster management; Industrial 4.0; IoT